Pelatihan Tourguide Di Desa Candipari, Kabupaten Sidoarjo - Wiwik Afifah; Sultoni Fikri; Rendy Dwi Syahputra; Gaung Agung Rachmatullah (CV. Era Digital Nusantara, 2024)
The tourguide training held by students of Universitas 17 Agustus 1945 Surabaya in collaboration with the Sidoarjo City Tourism Office is a strategic initiative to develop the tourism potential of Candi Pari Village, Sidoarjo. This activity aims to increase the capacity of the local community as professional tour guides, so that they are able to better manage and promote their village tourism destinations. The training covered a range of important aspects, from knowledge of local history and culture to practical skills in tour guiding. As the keynote speaker, the Sidoarjo City Tourism Office provided in-depth material on effective guiding techniques, ethics in guiding, and tourism marketing strategies. In addition, participants were also given training on sustainable and environmentally friendly tourism destination management. This direct interaction with experienced practitioners and speakers allowed participants to gain practical and applicable insights that can be directly applied in the field. Through this training, it is hoped that the people of Candi Pari Village can be more confident and competent in carrying out their roles as tour guides. The results of this training not only have an impact on improving the quality of tourist services, but are also expected to encourage local economic growth through a more organized and attractive tourism sector for tourists. Thus, the tourism potential of Candi Pari Village can be optimally and sustainably developed, providing long-term benefits for the local community.